Phospholipid Fatty Acid Profiles of Bacteria and Fungi in Peat Exposed to Experimentally Increased N Deposition, 2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). In July of 2015 we measured PLFA markers in two depths in each plot. For the most part, microbial group abundances were not affected by increasing N input (Fig. 16). However, actinomycete abundance decreased with increasing N deposition at rates that were similar in 0-5 and 5-10 cm peat. Gram-negative bacteria increased slightly with increasing N input and were more abundant in 0-5 cm than in 5-10 cm peat; correspondingly the Gram-positive to Gram-negative bacterial ratio decreased with increasing N input and was lower in 0-5 cm than in 5-10 cm peat. Total microbial abundance and total bacterial abundance were significantly higher in 0-5 cm peat than in 5-10 cm peat. It may be that more sensitive/targeted techniques, such as high-throughput pyrosequencing, 16s RNA clone library analysis and rRNA-targeted fluorescence in situ hybridization (FISH) or whole genome shotgun sequencing may be required to reveal bog microbial community responses to N loading.